ANALISIS FAKTOR PENDUKUNG IMPLEMENTASI TRANSAKSI NON TUNAI DENGAN PENDEKATAN ANALYTICAL HIERARCHY PROCESS (AHP) - Susanto, Adi (Fakultas Ekonomi Universitas 17 Agustus 1945 Cirebon, 2019)
Non-cash transactions in Indonesia are still low, one of which is triggered by the low involvement of small and medium enterprises (SMEs) retail in Indonesia who have not implemented non-cash transactions in their business environment. This study aims to analyze factors supporting the implementation of non-cash transactions in retail SMEs. The method used in this research is by Analytical Hierarchy Process (AHP) approach. The results of the study found that non-cash transactions implementation can be improved by maximizing potential carrying capacity: (1) Speed, (2) Security, (3) Efficiency / Practice, (4) Value of money, and (5) Government program. The main supporting factor that gets the highest priority is efficiency or practicality of 23%. Key word :Non-Cash Transactions, AHP, SMEs